2019
DOI: 10.1155/2019/1767203
|View full text |Cite
|
Sign up to set email alerts
|

Review on Cross Talk between Neurotransmitters and Neuroinflammation in Striatum and Cerebellum in the Mediation of Motor Behaviour

Abstract: Neurological diseases particularly Alzheimer's disease (AD), Parkinson's disease (PD), stroke, and epilepsy are on the rise all around the world causing morbidity and mortality globally with a common symptom of gradual loss or impairment of motor behaviour. Striatum, which is a component of the basal ganglia, is involved in facilitating voluntary movement while the cerebellum is involved in the maintenance of balance and coordination of voluntary movements. Dopamine, serotonin, gamma-aminobutyric acid (GABA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 70 publications
0
39
0
Order By: Relevance
“…Neuroinflammation in the cerebellum results in mild cognitive and motor impairment [ 23 ]. Our results showed in the cerebellum a significant increase in the expression of TNFα and IFNγ from day 1 and for IL-12 from day 14 post-infection ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroinflammation in the cerebellum results in mild cognitive and motor impairment [ 23 ]. Our results showed in the cerebellum a significant increase in the expression of TNFα and IFNγ from day 1 and for IL-12 from day 14 post-infection ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ketogenic diet- and EKSs-generated ketosis, βHB or the Deanna protocol, containing (among others) MCTs, can also generate alleviating effects on (i) motor neurons and motor performance in preclinical rodent models, such as animal models of amyotrophic lateral sclerosis [ 48 , 332 , 333 , 334 , 335 , 336 ] and (ii) dopaminergic neurons and motor performance in animal models of Parkinson’s disease [ 55 , 258 ] likely through improved mitochondrial function and ATP synthesis ( Table 1 ). Dysregulation of different neurotransmitter systems may have a role in the pathophysiology of neurodegenerative diseases, for example, in animal models and patients with impaired motor function (e.g., dopaminergic dysfunction; GABA and glutamate imbalance) [ 337 , 338 , 339 , 340 ], Parkinson’s disease (e.g., decrease in serotonin level and increase in glutamatergic transmission), Alzheimer’s disease (decreased cholinergic neurotransmission) and both Alzheimer’s disease and Parkinson’s disease (deficits in dopaminergic signaling) [ 337 , 339 , 341 , 342 , 343 ]. Moreover, dysfunctions in neurotransmitter systems (e.g., GABAergic, glutamatergic and cholinergic) can lead to impaired learning and memory [ 340 , 342 , 344 ].…”
Section: Alleviating Effects Of Ketosis On Lifespan Aging and Age-related Neurodegenerative Diseasesmentioning
confidence: 99%
“…Indeed, previous studies show that ketosis (βHB) may evoke therapeutic effects in the treatment of Alzheimer’s disease, Parkinson’s disease and amyotrophic lateral sclerosis and enhance learning and memory through anti-inflammatory effects induced by HCAR2 [ 50 , 55 , 57 , 58 , 275 , 279 ]. It was also demonstrated that enhanced expression of proinflammatory cytokines and oxidative stress have a role in the development of Alzheimer’s disease [ 276 , 356 , 357 ], Parkinson’s disease [ 55 , 276 , 356 , 357 ], amyotrophic lateral sclerosis [ 356 , 357 , 358 ], impaired motor functions [ 337 , 359 ] and impairment of learning and memory [ 309 , 310 , 360 ]. Thus, ketosis may also improve symptoms of neurodegenerative diseases, motor, learning and memory dysfunctions through anti-inflammatory and anti-oxidative effects via HCAR2 [ 50 , 275 , 361 ] ( Figure 2 ).…”
Section: Alleviating Effects Of Ketosis On Lifespan Aging and Age-related Neurodegenerative Diseasesmentioning
confidence: 99%
“…Neurotransmitters play a crucial part in the development and function of the nervous system, and slight changes in neurochemical levels may have significant impacts on the psychobehaviour of the subject (67). Glutamate, serotonin, gamma‐aminobutyric acid (GABA), and dopamine (just to name a few) interact in regulating physiological and psychiatric manifestations, such as emotion, behaviour, and cognition (68), while abnormalities in these neurotransmitters have been thought to be linked to ASD (69,70). Therefore, we hypothesize that the neurotransmitter system may have a particularly important mediating role in the association of aberrant methylation ability with ASD.…”
Section: Discussionmentioning
confidence: 99%